2021
DOI: 10.1080/00071668.2021.1955329
|View full text |Cite
|
Sign up to set email alerts
|

Integument, mortality, and skeletal strength in extended production cycles for laying hens – effects of genotype and dietary zinc source

Abstract: 1. This study on long-life layers, covering the period 20-100 weeks of age, investigated longitudinal effects on mortality, layer integument, and skeletal properties in Bovans White (BoW) and Lohmann Selected Leghorn Classic (LSL), with or without supplementation with dietary organic zinc (Zn).2. Two experiments, using 1440 layers in furnished small group cages (FC) and 1834 layers in a traditional floor housing system (Floor), were run in parallel. Each replicate consisted of five adjacent cages containing ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Supplementing diets with organic, bioavailable zinc, as compared to zinc made available through inorganic mineral salts (ZnO), did not significantly affect the skeletal integrity (measured using keel bone deformation) and mortality between 15 and 100 wk of age ( Wall et al, 2022 ). Bioavailability of essential compounds was also the focus in studying the effects of MBM and OSM.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementing diets with organic, bioavailable zinc, as compared to zinc made available through inorganic mineral salts (ZnO), did not significantly affect the skeletal integrity (measured using keel bone deformation) and mortality between 15 and 100 wk of age ( Wall et al, 2022 ). Bioavailability of essential compounds was also the focus in studying the effects of MBM and OSM.…”
Section: Resultsmentioning
confidence: 99%
“… Nannoni et al (2022) similarly indicated that worse plumage condition was found in birds with more freedom to move vertically in combi aviaries as time progressed. In another study on long-life layers, birds kept in a traditional floor housing system had a total feather score of less than 12 at 100 wk of age ( Wall et al, 2022 ). As the age of the birds increased, the condition of the hens' plumage deteriorated ( Sokołowicz et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported on egg quality ( Molnár et al, 2018 ; Jabalera et al, 2022 ), diseases ( Buyse et al, 2023 ), and physical condition ( Wall et al, 2022 ; van Eck et al, 2023 ) of hens near the end of the laying cycle. Furthermore, the high-intensity physical activity of hens declined with the increasing of age ( Kozak et al, 2016 ) which may lead to the increase of the population size of lower tier in the multitier system, and other issues of bird's health and resources allocation.…”
Section: Introductionmentioning
confidence: 99%
“…At 15 weeks of age, the pullets were transferred to the poultry experimental facility at the Swedish Livestock Research Centre Lövsta and subsequently housed either in furnished 8-hen cages or in a 1-tier floor housing system. The housing systems and management has been described in Wall et al . (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…As the dietary treatment was not significantly associated with bone strength (average difference of 1.7 N, P = 0.54 in a linear model including housing system and crossbred), we did not include diet in any of the further analyses in this paper. A detailed description of the organic zinc supplementation treatment and analyses of its effect on mortality, integument and bone strength was published in Wall et al . (2022) .…”
Section: Methodsmentioning
confidence: 99%